Factors Influencing with Surveillance and Control Behaviors for Dengue Hemorrhagic Fever among Village Health Volunteers in Mae Rim District, Chiang Mai Province - รัตนปัญญา, สิวลี (Ratchaphruek Journal, 2018)
This study was a cross-sectional descriptive study and aimed to evaluate the influencing of the predisposing factors, enabling factors and reinforcing factors that are related to surveillance and control behaviors for dengue hemorrhagic fever (DHF). Three hundred twenty one of village health volunteers (VHV), who lived in Mae Rim District, Chiang Mai Province, were participated in this study. Results showed the overall predisposing factors that are knowledge and attitude for surveillance and control of DHFwere fair-good. VHV were also more likely receive moderate-high level of enabling factors and high level of reinforcing factors. Moreover, almost of them were good practices for dengue surveillance and control activities.It also found that the attitude, the enabling factors and reinforcing factorscan be significantly predicted thedengue surveillance and control activities of VHV(R2 = 0.284;p = 0.007, < 0.001 and0.016, respectively). The findings suggested that DHF knowledge and attitude about the management of vector management index, removal potential mosquito breeding sites, strengthening skills in using resources to prevent dengue need to beemphasizedon VHV for sustainable control of dengue hemorrhagic fever in community.